Dual anti-cytokine biologic and/or targeted synthetic therapy combination in spondyloarthritis: a narrative review. Are we missing the opportunity for higher remission rates? - Vieira-Sousa, Elsa; Ávila-Ribeiro, Pedro; Fonseca, João Eurico (Frontiers in Medicine, 2025)
Spondyloarthritis (SpA) is a phenotypically heterogeneous group of diseases that share genetic and immune-mediated inflammatory pathways, affecting various organs/and tissues such as the synovium, enthesis, bone marrow, skin, eye, and bowel. Advances in understanding tissue-specific cytokine imbalance in SpA have unveiled an opportunity to foster higher remission rates through a more tailored cytokine blockade. Furthermore, over the years, the accumulated knowledge of the safety profile of approved anti-cytokine treatments has instilled confidence in considering the combination of two cytokine blockade agents for more severe musculoskeletal (MSK) or extra-MSK manifestations/in refractory patients. The rationale for these dual-targeted therapy combination strategies has largely depended on the predominant SpA manifestations and the known efficacy of these therapeutics in monotherapy. More recently, the addition of a targeted synthetic (ts) to a biologic (b) disease-modifying anti-rheumatic drug (DMARD) has also been considered. Additionally, newer bispecific anti-cytokine antibodies and tsDMARDs with dual mechanisms of action have been developed and assessed. Despite limited evidence from randomized controlled trials, real-world data from retrospective cohorts and case series/reports indicate that b/tsDMARD combinations are being used in clinical practice to overcome efficacy limitations of b/tsDMARD monotherapies in more severe either/or difficult-to-treat SpA patients, particularly in the presence of extra-MSK recalcitrant manifestations such as inflammatory bowel disease or psoriasis.